Transition metal thiophosphates Nb4P2S21: New kind of 2D materials for multi-functional sensors - Choi, Kyung Hwan; Oh, Seungbae; Chae, Sudong; Jeong, Byung Joo; Kim, Bum Jun; Jeon, Jiho; Lee, Sang Hoon; Yoon, Sang Ok; Woo, Chaeheon; Dong, Xue; Ghulam, Asghar; Lim, Changmo; et al. (Journal of Alloys and Compounds, 2021)
A new of 2D transition metal thiophosphates, Nb4P2S21, was synthesized through a vapor transport reaction. High purity and centimeter-scale large Nb4P2S21 crystals were obtained by controlling the growth temperature and stoichiometric ratio between niobium, phosphorus, and sulfur (using excess sulfur condition, Nb: P: S = 4: 2: 23). It was confirmed that large Nb4P2S21 crystals could be separated to a nanometer scale through mechanical exfoliation, and the exfoliated Nb4P2S21 layer exhibits semiconducting characteristics by measuring the change in electrical conductivity with temperature (increased conductivity with temperature in the range of 93–333 K). Furthermore, the device characteristics for detecting visible ray laser (635 nm) and NO2 gas molecules were verified. Based on these characteristics, the synthesized 2D material is expected to be a potential candidate for additional 2D materials and in multi-functional sensor devices, including optoelectronics and gas sensing applications.
Keywords: Device characteristics; Electrical conductivity; Gas sensing applications; Mechanical exfoliation; Multifunctional sensors; Nano-meter scale; Stoichiometric ratio; Vapor-transport reaction; 2D material; Gas sensor; Nb4P2S21; Photodetector; Transition metal thiophosphates